Association of Preoperative Biliary Drainage with Postoperative Morbidity after Pancreaticoduodenectomy. (22nd December 2015) - Liu, Chang; Lu, Jian-Wen; Du, Zhao-Qing; Liu, Xue-Min; Lv, Yi; Zhang, Xu-Feng
Abstract : Background . The advantages or disadvantages of preoperative biliary drainage (PBD) prior to pancreaticoduodenectomy (PD) remain unclear. Methods . A prospectively maintained database was queried for 335 consecutive patients undergoing standard PD surgery between 2009 and 2013. Clinical data and postoperative complications of the 47 patients receiving PBD and 288 patients with early surgery were compared. A matching analysis was also performed between patients receiving or not receiving PBD (no-PBD). Results . The indication for PBD was severe obstructive jaundice (81%) and cholangitis (26%) at the time of PBD. 47 PBD patients had higher bilirubin level than 288 no-PBD patients preoperatively (363.2 μ mol/L versus 136.0 μ mol/L, p < 0.001 ). Although no significant difference of any complications could be observed between the two groups, positive intraoperative bile culture and wound infection seemed to be moderately increased in PBD compared to no-PBD patients (p = 0.084 and 0.183, resp.). In the matched-pair comparison, the incidence of wound infection was three times higher in PBD than no-PBD patients (14.9% versus 4.3%, p = 0.080 ). Conclusions . PBD seems to moderately increase the risk of postoperative wound and bile duct infection. Therefore, PBD should be selectively performed prior to PD.